Densidade estomática e porosidade foliar de vinte espécies lenhosas encontradas no cerrado - Narcizo, Gerson Ricardo (Universidade Federal de São Carlos, 2002)
Stomatal density and leaf porosity of twenty woody species of cerrado vegetation. In this work was characterized the size, and density of stomata and leaf porosity of twenty woody species found in a cerrado vegetation located in the forest reserve of the Federal University of São Carlos SP. It was used paradermic cuts of mature leaf without tricomes. These cuts were observed in a microscopic acoplated a personal computer and stomata was counted and sized for the Image Plus program. The Casearia sylvestris presented the highest estomatal density: 602/mm2 in inferior surface and 316 /mm2 in the upper surface, however it presented the lesser average area of the stomatal porosity around 18.7 µm2 and 1.29% of total leaf porosity. The Kyelmeiera coriacea was placed in the other extremity of the stomatal density with 80/mm2 in the inferior surface of leaf and 43/mm2 in the upper surface. This species presented an high average of area pore, around 102 µm2 and total leaf porosity of 1.09%. The total leaf porosity for the studied species are distributed between 0.75 and 2.63% of the leaf surface. The Rapanea umbellata presented the biggest total leaf porosity for the group of twenty analyzed species, being around 2.63%, 230/mm2 for stomatal density and with 114µm2 of total area of pores. In the other extremity the Rapanea lancifolia presented the lesser leaf porosity, around 0.75% , 252/mm2 of stomatal density and 29.7µm of total area of pore. The results were analyzed in function of strategic adaptation of species to the hydric deficiency of cerrado biome.
Keywords: Estômato; Porosidade foliar; Densidade estomática; Cerrado; CIENCIAS BIOLOGICAS::ECOLOGIA